2008
DOI: 10.1021/la801868j
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Behavior of a Poly(ethylene glycol)-Grafted Phospholipid in Monolayers at the Air/Water Interface

Abstract: Mixed phospholipid monolayers hosting a poly(ethylene glycol) (PEG)-grafted distearoylphosphatidylethanolamine with a PEG molecular weight of 5000 (DSPE-PEG5000) spread at the air/water interface were used as model systems to study the effect of PEG-phospholipids on the lateral structure of PEG-grafted membrane-mimetic surfaces. DSPE-PEG5000 has been found to mix readily with distearoylphosphoethanolamine-succinyl (DSPE-succynil), a phospholipid whose structure resembles closely that of the phospholipid part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…< A 2 > . However, the true mean molecular area could not be accurately estimated for each component during the measurements due to attractive-repulsive forces between the component molecules and their complexations [30][31][32][33]. The mixture could be considered "ideal" if the component molecules have no irregular packing attachments, no complex formations, and form a phase separation in the monolayer [6,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…< A 2 > . However, the true mean molecular area could not be accurately estimated for each component during the measurements due to attractive-repulsive forces between the component molecules and their complexations [30][31][32][33]. The mixture could be considered "ideal" if the component molecules have no irregular packing attachments, no complex formations, and form a phase separation in the monolayer [6,30].…”
Section: Introductionmentioning
confidence: 99%
“…Different regions of the Langmuir isotherm can give information on the phase behavior of the molecules for each component. It was shown that more ordered and rigid monolayers collapse at relatively higher surface pressures, usually by fracturing, followed by loss of materials to the air side with the formation of multilayered aggregates, or to the sub phase with budding or vesicle formation [25,29,31,34]. When a binary mixture of components having two different collapse pressures were compressed, at least two plateaus will exhibit, one is at the lower collapse pressure for the expanded phase and the other is at the higher collapse pressure for the more rigid component [6,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in saline-containing aqueous solutions have reported that PEG hydration and conformational behavior can be affected by saline in a way not easily predictable by existing theories. Moreover, interactions with saline may influence the miscibility and phase of constituents of PEG-grafted lipid surfaces . Although much has been learned about the self-assembly of lipids and PEG−lipid conjugates, , the effect of saline on their miscibility, phase, and conformational behavior at surfaces and interfaces has not yet been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…Among various model systems, PEG−lipid monolayers at the air/water interface have proven to provide ideal models of PEG-grafted lipid surfaces. , The advantage of these monolayers as model systems is that they allow the precise control of parameters such as lateral (surface) pressure and area per lipid molecule, which is not possible with bilayers and liposomes/vesicles. Wide range variations of PEG grafting density can be easily simulated in a well-controlled manner by the monolayer compression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation